Kliping (Kelompok Ibu Pendamping Gizi) Sebagai Upaya Peningkatan Status Gizi Balita Malnutrisi di Kecamatan Mantrijeron Yogyakarta - Huriah, Titih; Sakinah, Isnina Noor; Noorzanah, Noorzanah; Kunak, Andinayanti (Jurnal Keperawatan Komunitas, 2015)
Basic Health Research in 2010 showed that the prevalence of malnutrition in Yogyakarta was 1.4%. WHO since 2007 has socialized a Community-Based Management of Severe Acute Malnutrition programs to handled the malnutrition problem which one of activities was forming Self Help Group (SHG) in society. KLIPING is one of the SHG programs to give support each other and share experiences to mother who has same problem with malnourished children. This research is aimed to improve nutritient status of children under five with malnutrition by KLIPING program in Mantrijeron Sub District Yogyakarta. Quasi-experimental with pretest-posttest control group design was carried out in this study. 25 children with malnutrition were selected using purposive sampling, 11 children for intervention group and 14 childrens for control group. The analysis conducted used statistic test of Paired t-test and Independent ttest. The results showed there is increases of z score in the intervention group with p value 0.030, while there was no increase in the Z Score differences both of two groups before and after the KLIPING intervention. During 2 months intervention of KLIPING (Nutrition Supporting Group) there was significant increases of z score in intervention group.